2016
DOI: 10.1186/s12906-016-1239-1
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary assessment of free radical scavenging, thrombolytic and membrane stabilizing capabilities of organic fractions of Callistemon citrinus (Curtis.) skeels leaves

Abstract: BackgroundCallistemon citrinus (Curtis.) (Family- Myrtaceae) is a popular evergreen shrub in Bangladesh. In the present study, the leaves of this plant have been assessed comprehensively for free radical scavenging, thrombolytic and membrane stabilizing activities.MethodsThe leaves were collected, powdered and extracted with methanol. The extract was then concentrated and successively fractionated into petroleum ether, carbon tetrachloride, chloroform and aqueous soluble fractions. The extractives were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Here also it is clear that the last fraction of the successive extraction procedure, which acts as the most potent antioxidant fraction, is rich in bioactive phytochemicals and extracted with the most polar solvent. An earlier study indicated that the crude leaf methanolic extract of C. citrinus and its extract fractions have differential free radical scavenging potentials and that also supports our findings that water is more suitable than petroleum ether for extracting bioactive antioxidant molecules from C. citrinus leaf 23 . Recently, through a comparative study, our laboratory reported that the successive leaf aqueous extract fraction of Crinum asiaticum having the highest antioxidant and antibacterial potentials along with the highest phenolics contents 8 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Here also it is clear that the last fraction of the successive extraction procedure, which acts as the most potent antioxidant fraction, is rich in bioactive phytochemicals and extracted with the most polar solvent. An earlier study indicated that the crude leaf methanolic extract of C. citrinus and its extract fractions have differential free radical scavenging potentials and that also supports our findings that water is more suitable than petroleum ether for extracting bioactive antioxidant molecules from C. citrinus leaf 23 . Recently, through a comparative study, our laboratory reported that the successive leaf aqueous extract fraction of Crinum asiaticum having the highest antioxidant and antibacterial potentials along with the highest phenolics contents 8 .…”
Section: Discussionsupporting
confidence: 89%
“…Leaves and flowers of C. citrinus constitute a major compound, 1-(2,6-dihydroxy-4-methoxyphenyl)-3-methylbutan-1-one (phloroglucinol) which was reported for potent dose-dependent antinociceptive and anti-inflammatory properties correlating its strong in vivo antioxidant activity 22 . Different medicinal properties like thrombolytic, membrane-stabilizing, free radical scavenging and anti-inflammatory potentials of the different organic solvent-mediated leaf extracts of C. citrinus were studied and revealed to be very promising 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Stabilization of the lysosomal membrane is necessary to limit the inflammatory response through inhibition of the release of lysosomal constituents of activated neutrophils such as proteases and bactericidal enzymes. Exposure of erythrocytes to a hypotonic medium results in membrane lysis [31]. A possible mechanism for membrane stabilization activity of Callistemon essential oil observed herein could be attributed to the ability of essential oil constituents to integrate into cellular membranes, increasing the surface area to volume ratio of the cells that might be brought about by expansion of the membrane or shrinkage of the cell, as well as an interaction with membrane proteins [17].…”
Section: Resultsmentioning
confidence: 99%
“…Ahmed et al reported that C . citrinus chloroform fraction exhibited membrane stabilizing anti-inflammatory potentials in hypotonic solution-induced hemolysis, results were comparable to acetylsalicylic acid, the standard drug [31].…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic content in the plant extractives is a sign of antioxidant potentials, which can be measured by using Folin-Ciocalteu reagent. 11 By using gallic acid as standard, the highest phenolic content was found in MEAM (305.61 mg of GAE/g of extractives). The order of phenolic contents in the extractives was MEAM > CTCAM > CAM > PEAM (Figure 2a).…”
mentioning
confidence: 96%